Dynamic Alterations of the Distal Intestinal Microbiota, Transcriptome, and Metabolome of Hybrid Grouper by β -Conglycinin With Reconciliations by Sodium Butyrate in Feed - Yin, Bin; Liu, Hongyu; Tan, Beiping; Dong, Xiaohui; Chi, Shuyan; Yang, Qihui; Zhang, Shuang (Frontiers in Marine Science, 2021)
Different doses of β-conglycinin produce different regulations on the intestinal health of aquatic animals, affecting the absorption of nutrients, indirectly changing water quality. Sodium butyrate (NaB) can effectively alleviate the negative effects caused by high-dose β-conglycinin. We investigated the positive response to low-dose (1.5%, bL) and negative response to high-dose (6.0%, bH) β-conglycinin and supplementation with NaB (6.0% β-conglycinin + 0.13% NaB, bHNaB) in terms of water pollutants, microbiota, transcriptome, and metabolome in hybrid grouper (Epinephelus fuscoguttatus♀ × E. lanceolatus♂). The ammonia nitrogen, nitrite, total nitrogen, and total phosphorus contents were significantly higher in the water from bH than from FMb, bL, and bHNaB. Supplementing with NaB significantly reduced the ammonia nitrogen, nitrite, total nitrogen, and total phosphorus contents. Low-dose β-conglycinin increased the relative abundance of Pelagibacterium, Pediococcus, Staphylococcus, and Lactobacillus and promoted the “ribosome,” “peroxisome proliferator-activated receptor (PPAR) signaling” and “histidine metabolism.” High-dose β-conglycinin increased the relative abundance of pathogenic bacteria Ralstonia and Photobacterium and inhibited the “cell cycle” “PPAR signaling” and “starch and proline metabolism.” NaB supplementation at high-dose β-conglycinin reduced the Ralstonia and Photobacterium abundance and promoted the “cell cycle,” “linoleic acid metabolism,” and “ABC transporters.” Overall, these results reveal differences in the effects of high- and low-dose β-conglycinin, as well as NaB supplementation, on the utilization of proteins, carbohydrates, and lipids and on substance transport and signaling among distal intestinal cells of hybrid grouper. A total of 15 differential metabolite biomarkers were identified: FMb vs. bL contained 10-methylimidazole acetic acid, N-acetyl histamine, urocanic acid, creatinine, glutathione, taurine, nervonic acid, stearic acid, docosanoic acid, and D-serine; FMb vs. bH contained 4-L-fucose, sucrose, α,α-trehalose, and quercetin; and bH vs. bHNaB contained 4-N-acetyl histamine, urocanic acid, creatinine, and S-adenosylhomocysteine, respectively. Our study provides new insights into the regulation of intestinal health by β-conglycinin in aquatic animals and the protective mechanism of NaB.